From bare to birch : large-scale ecosystem restoration in Iceland - Orradottir, Berglind; Barrio, Isabel C.; Boyaninska, Daniela (London : Rotterdam School of Management, Erasmus University, 2019)
The case of Hekluskógar (meaning "Hekla woodlands") in South Iceland examines how to transition from barren desertified land to a resilient and healthy woodland that can provide ecosystem services to the people in the area and beyond. The case provides a thorough description and background of the many components involved in the largest reforestation project in Europe as of 2018.
Originally Published InOrradottir, B., Barrio, I. C., & Boyaninska, D. (2019). From Bare to Birch:Large-Scale Ecosystem Restoration in Iceland. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Restoration ecology -- Iceland